Legal Effects Of Bankruptcy On Marital Couples Without A Marital Agreement : (Analysis Of Supreme Court Decision Number: 510/PDT.G/2019/PN JKT.SEL) - Herpandu Hadiwibowo (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
Male and female couples marry to have offspring. If a couple does not have a marriage agreement, it could affect the property they own together, especially if one goes bankrupt. This research is descriptive-analytical research that leads to normative juridical research. Based on the research results, it is found that in bankruptcy, the debtor (husband) cannot pay and settle debts with his creditors, resulting in a joint property without a marriage agreement being included in the bankruptcy. As a result of this decision, the debtor's wife did not accept. She filed a lawsuit with the South Jakarta District Court (Decision of the Supreme Court of the Republic of Indonesia Number 510/Pdt.G/2019/PN Jkt.Sel). It was stated that the lawsuit could not be accepted or rejected because the South Jakarta District Court lacked the authority to examine and decide on bankruptcy cases. According to the results, the union of property is the union of assets and the burden of payment. The legal consequences of marital property without a marriage agreement, if one of the parties falls into bankruptcy, the bankruptcy of the husband and wife against their joint property through a court decision will be considered joint bankruptcy by the provisions in Article 64, Paragraph 1, of Law No. 37 of 2004.